Professional development perspectives across gender and age groups of under-qualified rural NEETs - Almeida, A. (2020)
Our study explored how self-efficacy perceptions are associated with Perceived Barriers (PB), meaning beliefs about constraints on current/future vocational development, and Professional Expectations (PE) among rural, under-qualified youths Not in Employment, nor in Education or Training (NEET). We also analyzed how the connections between these factors varied across gender and age groups. One-hundred and eighty eight NEETs participated in this study (58.20% female; (M = 23.05; SD = 1.96). Through linear regression analysis using PROCESS macros we found that higher self-efficacy was associated with stronger PB, after accounting for the effects of training offers and income. Moreover, men showing stronger self-efficacy also displayed stronger PB, while men depicting weaker self-efficacy presented weaker PB, compared to women in similar conditions. Being offered more training opportunities resulted in stronger perceptions of professional barriers for these NEETs. Thus, rural, under-qualified NEETs require person-centered approaches from employment services, to support their transition to employment/training.